Closing a Backdoor to Dual Citizenship: The German Citizenship Law Reform of 2000 and the Abolishment of the “Domestic Clause” - Falcke, Swantje; Vink, Maarten (Frontiers in Sociology, 2020)
The German citizenship law underwent a paradigmatic amendment in 2000. One often overlooked change of this reform was the abolishment of the domestic clause (‘Inlandsklausel’) that implied a substantial restriction to de facto dual citizenship acceptance. Combining data from the German Socio-Economic Panel Study (waves 1993-2006) with original data on origin country policies on dual citizenship and citizenship reacquisition, we analyse the impact of the abolishment of the domestic clause on naturalisation rates. We apply a difference-in-difference design to investigate the causal impact of this element of the reform which has remained under-studied. We do not find an impact of the abolishment of the domestic clause on naturalisation rates, neither among the general migrant population, nor among Turkish migrants who are alleged to be targeted specifically by this reform. These results suggest that a more restrictive approach to dual citizenship did not dissuade migrants from acquiring German citizenship after 2000.